Relationship Duration and Returns to Brokerage in the Staffing Sector - Bidwell, Matthew; Fernandez-Mateo, Isabel (Organization Science, 2010)
We examine how long-term relationships affect brokers' returns, using project-level pricing data from an information technology staffing firm. We argue that long-term relationships between brokers and their counterparties affect both acquisition of private information and bargaining power, helping brokers to create and capture economic value. The results show that the staffing firm is able to charge a higher price and capture a higher proportion of that price when it has a long-term relationship with the worker. We also show that the staffing firm's ability to generate returns from its relationships is constrained when the brokered parties (worker and client firm) have a long-term relationship with each other. We discuss the implications of these findings for the study of market brokerage and long-term exchange relationships.